Caesarean scar pregnancy: a rare case report - Varadhan, Vardhani; Gopalan, Ushadevi; Mayilvahanan, Karthika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Cesarean scar pregnancy (CSP) is a rare and potentially dangerous form of ectopic pregnancy occurring when a blastocyst implants in the cesarean section scar, leading to abnormal gestational development between the myometrium and the scar tissue. Incidence ranges from 1/1800 to 1/2500 pregnancies and is increasing with rising cesarean delivery rates. CSP commonly presents with abdominal pain and vaginal bleeding. Diagnosis is facilitated by transvaginal sonography, and MRI is valuable when sonography results are inconclusive. A case of a 27-year-old woman with a previous cesarean section is reported, presenting with elevated beta-hCG and an ultrasound revealing a fetal pole in the lower uterine segment with minimal myometrium between the scar and the gestational sac. The patient underwent laparotomy and excision of the scar pregnancy, with histopathological examination confirming chorionic villi invasion through the myometrium. CSP is categorized into three types based on myometrial thickness and location, each with varying risks and management strategies including medical treatment, surgical intervention, and a combination of methods. Early diagnosis and management are crucial to avoid severe complications, with decision-making guided by the patient’s future fertility desires.